Effectiveness of Regulation and Law Enforcement against Illegal Investment Organizers Post-P2SK Law - Mulyana, Septira Putri; Sumaragatha, I Gusti Bagus Sakah (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
Illegal investments in Indonesia cause substantial public losses and threaten financial system stability. This study analyzes legal threats against illegal investment operators and evaluates the effectiveness of Law No. 4 of 2023 on Financial Sector Development and Strengthening (P2SK Law) in protecting the public. Using a normative legal method with statute and conceptual approaches, the study examines legislation, legal literature, and official publications from the Financial Services Authority (OJK). Findings show that the P2SK Law explicitly prohibits unauthorized fundraising (Article 237) and imposes strict sanctions, including 5-10 years imprisonment and fines up to IDR 1 trillion (Article 305). OJK Regulations 22/2023 and 14/2024 strengthen preventive and enforcement mechanisms through integrated supervision and Satgas PASTI. The study concludes that P2SK significantly enhances legal protection and deterrence against illegal investments. Strengthening financial literacy, optimizing Satgas PASTI, and consistent law enforcement are essential for effective public protection and sustainable financial stability.